Artificial Intelligence: The Perspectives Of Undergraduate Level Second Language Learners (Journal of Pharmaceutical Negative Results, 2023)
The Artificial Intelligence (AI) has seen significant advancements in recent decades. As a result of the development of a diversity of platforms, it has been put to use in ways that have never been seen before in a variety of fields and disciplines, including the fields of data science, information science, online marketing, and data mining. Additionally, it has been utilised in the field of “connected” objects. Since the development of artificial intelligence, there has been a steady march towards widespread computing. Computing technology is becoming more “intelligent” and capable of anticipating our everyday need, with the ultimate objective of assisting us in being more fruitful in the lengthy time. This technology is utilised extensively in both our personal and professional life on a day-to-day basis. The installation of an app in a computing gadget, with or without the use of artificial intelligence, is what we mean when we talk about technology in this context. Despite this, the incorporation of AI into apps for language acquisition is still largely underutilised.